The Co-Design Curriculum Mandate Policy Addresses the Misalignment Between Vocational Madrasah Aliyah Graduates and Industry Needs - Unwan Maika (JURNAL ILMIAH GEMA PERENCANA, 2026)
The low competitiveness of Vocational Madrasah Aliyah (MAK) graduates in the labor market is a strategic issue rooted in the misalignment of competencies with current industrial needs. This mismatch phenomenon is exacerbated by the slow pace of adaptation to technological disruption as well as bureaucratic procedures and national standardization that tend to be rigid in responding to market dynamics. This analysis aims to formulate policy transformation to enhance practical skills and graduate relevance through the strengthening of adaptive and flexible curricula. The policy methodology applied in this study utilizes a qualitative approach based on literature review and legislative analysis to dissect the vocational education regulatory framework. The problem identification process is conducted through priority assessment instruments using Urgency, Seriousness, and Growth (USG) criteria to identify the most crucial root causes. Furthermore, various policy alternatives are evaluated in depth using criteria of effectiveness, efficiency, adequacy, responsiveness, and appropriateness to ensure the generated recommendations possess a strong implementation basis. The findings indicate that a policy mandating the co-design of the curriculum between madrasah institutions and industrial associations is a fundamental solution to shift the educational paradigm from supply-based to labor market demand-driven. The primary recommendation in this policy paper is to urge the Minister of Religious Affairs of the Republic of Indonesia to issue regulations requiring the synchronization of operational curricula with industrial stakeholders as an absolute prerequisite for document legality.